How to implement a clinical ethics committee in an oncological research hospital: Qualitative results from a process evaluation study using normalization process theory (EVACEC) - Marta Perin; Morten Magelssen; Chiara Crico; Luca Ghirotto; Marco Annoni; Giorgio Gualandri; Ludovica De Panfilis (PLoS ONE, 2025)
Introduction The Clinical Ethics Committee (CEC) of the Local Health Authority (LHA) of Reggio Emilia, Italy, is a multi-professional service established in 2020 to support healthcare professionals (HPs) in dealing with ethical issues in clinical practice. We evaluated the integration of the CEC into routine practice, 24 months after its implementation. Methods We conducted semi-structured interviews with CEC members and LHA stakeholders involved in the service implementation. The interview scripts were outlined and transcript analysis was carried out following the four concepts of Normalization Process Theory (NPT): coherence, cognitive participation, collective action, reflexive monitoring. Results Between June 2022 and January 2023, 15 participants were interviewed (12 CEC members and 3 LHA directors). All participants consider the service an important opportunity for HPs to be supported in complex situations (coherence). The CEC’s President, a bioethicist working at the LHA, played a key role ensuring the CEC’s participation and activation (cognitive participation). The main barriers to the CEC implementation were: financial sustainability, CEC members’ lack of training, absence of in-person relationships (collective action). Overall, participants reported a positive experience with the CEC, however recommended several modifications (reflexive monitoring). Conclusions We identified key components to support the normalization of CECs and enable their activation within a clinical setting. An active and sustainable CEC must be visible, accessible, understood and trusted, clear in purpose, sufficiently integrated into the life of the organisation, adequately resourced, appropriately constituted and competent, accountable and independent. These findings can inform the development of practical strategies for CECs implementation and of appropriate outcomes for further evaluation.